Developing Android App-Based Interactive Learning Media for Mechanical Engineering Basics: Enhancing Vocational School Student Learning Outcomes - Arief Juneirul Pratama; Arwizet K; Hasan Maksum; Rizky Ema Wulansari (Jurnal Penelitian Pendidikan IPA, 2024)
This study is to provide valid, practical, and effective Android application-based interactive learning media for the Basics of Mechanical Engineering subject in class X Mechanical Engineering at SMK Dhuafa Padang. This medium is intended to boost students' comprehension, motivation, and independence, allowing them to achieve better learning outcomes. The research approach employed is Research and Development (R&D), using a 4D development model (define, design, develop and disseminate). The primary data utilized in this study came from validators, teachers, and students. Data was analyzed descriptively to characterize the validity, practicality and effectiveness of the learning media developed. The validity test findings show that this learning medium, which had a media aspect score of 0,892 and a material aspect score of 0,950, was deemed valid by expert review. This media was also declared practical with a practicality score of 96,94% from teacher responses and 92,25% from student responses. In the effectiveness test, the Gain Score was 0,68, placing it in the medium category. Meanwhile, the t-test shows a Sig value (2-tailed) of 0.002 (2-tailed < 0,05) and a tcount value of 3,372 (tcount ˃ ttable), indicating a significant difference in learning outcomes between students who use this learning media (experimental class) and those who do not use the media (control class). Thus, this Android application-based interactive learning media is declared valid, practical and effective for use in the DDTM learning process.